The role of grain-boundary cementite in bainite formation in high-carbon steels. (August 2020) - Ravi, Ashwath M.; Sietsma, Jilt; Santofimia, Maria J.
Graphical abstract: Abstract: Low temperature bainite formation in high-carbon steels leads to highly refined microstructures. However, the rate of bainite formation becomes impractically low as the bainite formation temperature decreases. Thus, it is important to create strategies to accelerate the low-temperature bainite formation kinetics in high-carbon steels. In this work, it is observed that decorating the parent austenite grain boundaries with grain-boundary cementite prior to bainite formation leads to an appreciable acceleration of subsequent bainite formation kinetics due to decrease in activation energy for bainite nucleation at cemenite/austenite interfaces.